2020
DOI: 10.1515/nanoph-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

Advances in exploiting the degrees of freedom in nanostructured metasurface design: from 1 to 3 to more

Abstract: The unusual electromagnetic responses of nanostructured metasurfaces endow them with an ability to manipulate the four fundamental properties (amplitude, phase, polarization, and frequency) of lightwave at the subwavelength scale. Based on this, in the past several years, a lot of innovative optical elements and devices, such as metagratings, metalens, metaholograms, printings, vortex beam generators, or even their combinations, have been proposed, which have greatly empowered the advanced research and applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 164 publications
(337 reference statements)
0
17
0
Order By: Relevance
“…By manipulating light's properties with a more degree of freedom, various metasurfaces have been proposed recently to construct specific light field distribution in the near‐ and far‐field. [ 20–37 ] The near‐field is the region where light's propagation distance is much less than one wavelength, while the far‐field denotes the region in which light propagates far beyond one wavelength. [ 38 ] Enabled by dividing the metasurfaces into several segments corresponding to different functionalities, the stacking, [ 23–25 ] segmenting, [ 28 ] or interleaving metasurfaces [ 29 ] can implement the integration of the near‐ and far‐field functionalities.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…By manipulating light's properties with a more degree of freedom, various metasurfaces have been proposed recently to construct specific light field distribution in the near‐ and far‐field. [ 20–37 ] The near‐field is the region where light's propagation distance is much less than one wavelength, while the far‐field denotes the region in which light propagates far beyond one wavelength. [ 38 ] Enabled by dividing the metasurfaces into several segments corresponding to different functionalities, the stacking, [ 23–25 ] segmenting, [ 28 ] or interleaving metasurfaces [ 29 ] can implement the integration of the near‐ and far‐field functionalities.…”
Section: Figurementioning
confidence: 99%
“…DOI: 10.1002/adma.202007507 in the near-and far-field. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The nearfield is the region where light's propagation distance is much less than one wavelength, while the far-field denotes the region in which light propagates far beyond one wavelength. [38] Enabled by dividing the metasurfaces into several segments corresponding to different functionalities, the stacking, [23][24][25] segmenting, [28] or interleaving metasurfaces [29] can implement the integration of the near-and far-field functionalities.…”
mentioning
confidence: 99%
“…[6][7][8][9][10] By skillfully tailoring the subwavelength nanostructure parameters, the optical response of each unit of a metasurface can be independently and completely controlled. [11,12] Previous works have demonstrated that such artificial planar material has powerful functionalities for manipulating light wave with multiple degrees of freedom, [13][14][15][16][17][18][19] which make various applications experimentally demonstrated in visible regime. Moreover, the application scenarios of such metasurface in holographic 3D imaging and information encryption are also demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…focused on the design of the metasurfaces with the nanoscatterers taking different shapes, different dimensions, and various rotation angles, and reviewed the related basic and applied studies in light field manipulation including the optical vortices. [ 25 ] Chen et al. summarized the researches about the phase control of metasurfaces and the applications in wave front manipulation, holography imaging, and parallel output.…”
Section: Introductionmentioning
confidence: 99%